Thermospheric Density Perturbations Produced by Traveling Atmospheric Disturbances During August 2005 Storm. Issue 2 (9th February 2022) - Pham, K. H.; Zhang, B.; Sorathia, K.; Dang, T.; Wang, W.; Merkin, V.; Liu, H.; Lin, D.; Wiltberger, M.; Lei, J.; Bao, S.; Garretson, J.; et al.
Abstract: Thermospheric mass density perturbations are commonly observed during geomagnetic storms and fundamental to upper atmosphere dynamics, but the sources of these perturbations are not well understood. Large neutral density perturbations during storms greatly affect the drag experienced by low Earth orbit. We investigated the thermospheric density perturbations at all latitudes observed along the CHAMP and GRACE satellite trajectories during the August 24–25, 2005 geomagnetic storm. Observations show that large neutral density enhancements occurred not only at high latitudes, but also globally. Large density perturbations were seen in the equatorial regions away from the high‐latitude, magnetospheric energy sources. We used the high‐resolution Multiscale Atmosphere Geospace Environment (MAGE) model to simulate consecutive neutral density changes observed by satellites during the storm. The MAGE simulation, which resolved mesoscale high‐latitude convection electric fields and field‐aligned currents, and included physics‐based specification of auroral precipitation, was contrasted with a standalone ionosphere‐thermosphere simulation driven by a high‐latitude electrodynamics empirical model. The comparison demonstrates that first‐principles representations of highly dynamic and localized Joule heating events in a fully coupled whole geospace model is critical to accurately capture both generation and propagation of traveling atmospheric disturbances (TADs) that produce neutral density perturbations globally. The MAGE simulation shows that larger density peaks in the equatorial region observed by CHAMP and GRACE are the result of TADs generated at high‐latitudes in both hemispheres, and intersect at low‐latitudes. This study reveals the importance of investigating thermospheric density variations at all latitudes in a fully coupled geospace model with sufficiently high resolving power. Plain Language Summary: During geomagnetic storms, increased activity within the geospace environment causes large scale plasma convection to occur and electrons to precipitate into the upper atmosphere. The enhanced heating of the thermosphere by the plasma convection and electron precipitation can produce large perturbations in the neutral density. These neutral density perturbations propagate away from their point of origin, oftentimes traveling to the equator and into the other hemisphere. Here, simulation results using a high resolution coupled geospace model that includes a magnetosphere, inner magnetosphere, ionosphere, and thermosphere model show that neutral density perturbations generated in one hemisphere can propagate far enough to interact with those in the other hemisphere. The intersection of two or more perturbations produce regions of larger neutral density perturbations. The high resolution coupled geospace model performs significantly better than the standalone model when compared to observations of neutral density by low altitude spacecraft. A significant fraction of the observed neutral density perturbations is captured by the coupled model, especially those at low latitudes. Proper simulation and understanding of storm‐time neutral density perturbations is imperative to space weather prediction as neutral density perturbations can greatly affect satellite drag. Key Points: Most neutral density peaks observed by CHAMP and GRACE during a geomagnetic storm are associated with traveling atmospheric disturbances TADs generated at high‐latitudes propagate globally and intersect to produce large amplitude enhancements at low latitudes A coupled geospace model with high spatial resolving power is necessary to properly resolve TADs observed by CHAMP and GRACE